Factors for the Formation of Adjusted Net Savings in the People’s Republic of China - RUDENKO-SUDARIEVA, Larysa V.; SHEVCHENKO, Yuliia A. (Journal of Advanced Research in Law and Economics, 2019)
The study investigates the fundamental issues concerning Adjusted Net Savings (ANS) as one of the most objective indicators of modern country development assessment. Due to its complex structural nature, this indicator includes several groups of factors influencing the changing environment of countries or regions. The purpose of this study was to identify the impact of factors on adjusted net savings as a major indicator of welfare and wealth in modern turbulent environment and to look for new measures of economic development in any country. The use of the adjusted net savings indicator is the result of long reflections, studies, comparisons of World Bank scientists, the European Commission, who acknowledge the loss of universality and diminished relevance of the GDP indicator and support the concept of sustainable development, which implies economic prosperity, closing the gap between the levels of income in different strata of the population, increasing environmental literacy and integrity, reducing energy dependency. It was found that each country had its own features and conditions for the formation of savings, which were selected with consideration of the impact on GDP and on adjusted net savings. But at this stage of the study, we have selected only the main factors that confirm the importance of considering the environmental and social component of sustainable development of the country.As a result, the following key factors in generating adjusted net savings are highlighted: education costs, energy depletion, and natural resource depletion, which is linked to sustainable development for future generations.